2021
DOI: 10.1128/jb.00034-21
|View full text |Cite
|
Sign up to set email alerts
|

Pilus Production in Acinetobacter baumannii Is Growth Phase Dependent and Essential for Natural Transformation

Abstract: Acinetobacter baumannii is a severe threat to human health as a frequently multidrug-resistant hospital-acquired pathogen. Part of the danger from this bacterium comes from its genome plasticity and ability to evolve quickly by taking up and recombining external DNA into its own genome in a process called natural competence for transformation. This mode of horizontal gene transfer is one of the major ways pathogens can acquire new antimicrobial resistances and toxic traits. Because these processes in A. bauman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 94 publications
5
60
1
Order By: Relevance
“…Furthermore, A. baumannii DNA uptake by A. baumannii occurs while moving across wet surfaces [12]. Further studies refined our understanding of natural competency, which shows a correlation with growth phase-dependent synthesis of a type IV pilus [26]. The studies briefly described above conclusively showed that motility and natural competence are intimately associated.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, A. baumannii DNA uptake by A. baumannii occurs while moving across wet surfaces [12]. Further studies refined our understanding of natural competency, which shows a correlation with growth phase-dependent synthesis of a type IV pilus [26]. The studies briefly described above conclusively showed that motility and natural competence are intimately associated.…”
Section: Introductionmentioning
confidence: 79%
“…To determine the effect of the H-NS global regulator in natural transformation, we deleted the gene in two experimentally validated A. baumannii strains and determined the expression of competence-associated genes. Pilus-related genes and twitching motility are essential for A. baumannii's transformability [8,26]. Therefore, we compared the expression levels of pilA, pilT, pilQ, comEA, comEC, comF, and drpA in the wild type, the Δhns, and a complemented strains.…”
Section: H-ns Role In Natural Transformation In the First Naturally Competent Acinetobacter Baumannii Clinical Isolatementioning
confidence: 99%
See 1 more Smart Citation
“…This profile was similar to that observed for other related bacteria, such as C. jejuni , C. coli or H. pylori , with the natural transformation occurring at all the growth phases as well, although for these species, the frequency of transformation reaches a peak at the mid-exponential phase [ 18 , 19 , 41 ]. However, the regulatory pathways of natural transformation are divergent according to bacterial species/genera [ 13 , 42 ], and the most efficient process can occur at different growth phases, either when DNA is added prior to the exponential phase [ 41 ], during the exponential phase [ 18 , 19 , 43 , 44 ] or during the late-log to mid-stationary phase [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent works indicate that ARGs-containing bacteriophages might contribute to AR spread in this microorganism [ 153 , 154 ]. Finally, it has been recently found that this organism can be naturally competent [ 155 , 156 ], opening the possibility that direct transformation could be a relevant mechanism triggering the acquisition of ARGs by this bacterium.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%